Culture in communication : analyses of intercultural situations - Di Luzio, Aldo; Günthner, Susanne; Orletti, Franca (Pragmatics & beyond, 2001)
This volume is dedicated to questions arising in linguistic, sociological and anthropological analyses of intercultural encounters. It aims at presenting new theoretical and methodological aspects of Intercultural Communication, focusing on issues such as ideology and hegemonial attitudes, communicative genres and culture specific repertoires of genres, the theory of contextualization and nonverbal (prosodic, gestural, mimic) contextualization cues. The collected articles, which share an interactive view of language, focus on the methodological possibilities of explanatory analyses of intercul.